2010
DOI: 10.1007/s10722-009-9504-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic relationships between wild and cultivated Brassica oleracea L. with emphasis on the origination of cultivated crops

Abstract: Wild taxa in Brassica oleracea L. play an important role to improve cultivated crops, but the genomic relationships between wild and cultivated forms have not been well clarified. An overall survey of genomic relationships among 39 accessions covering 10 wild and 7 cultivared types in B. oleracea was performed using amplified fragment length polymorphism and simple sequence repeat. The cultivated types were clustered together with B. oleracea ssp. oleracea, B. incana, B. bourgeaui, B. montana, B. cretica and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
6
18
0
2
Order By: Relevance
“…However, unexpectedly B. cretica as a member of the B. oleracea cytodeme clustered within the same group. The remaining B. oleracea genotypes were found in clusters 2, 3, and 5, thus confirming earlier reports describing B. oleracea as an 'incredible diverse' species (Mei et al 2010; and references therein). Cluster 2 is linked to the B. rapa cluster 1 with a weak bootstrap value of less than 50 % (data not shown).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, unexpectedly B. cretica as a member of the B. oleracea cytodeme clustered within the same group. The remaining B. oleracea genotypes were found in clusters 2, 3, and 5, thus confirming earlier reports describing B. oleracea as an 'incredible diverse' species (Mei et al 2010; and references therein). Cluster 2 is linked to the B. rapa cluster 1 with a weak bootstrap value of less than 50 % (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…oleracea 7695 and cultivated B. oleracea forms in cluster 5. The (Lázaro and Aguinagalde 1998a,b;Allender et al 2007;Mei et al 2010). In the present study, Brassica insularis grouped together with B. hilarionis and B. napus genotypes in cluster 2.…”
Section: Discussionsupporting
confidence: 57%
“…However, our data could suggest that there is tremendous genetic potential to improve rapeseed resistance against S. sclerotiorum with wild types of B. oleracea, such as B. rupestris, B. incana, B. insularis and B. villosa which were found to possess high level of resistance. It is interesting to mention that these four wild types of B. oleracea which mainly distributed in Sicily, Italia (Snogerup et al 1990), possess similar genetic background with each other, and exhibit genetic diversity from the other types of B. oleracea (Lannér et al 1997;Lázaro and Aguinagalde 1998a, b;Mei et al 2010b). Whether the Sicilian region represents one of the resistance source centres against S. sclerotiorum needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity within B. oleracea crops appears to be generally lower than within wild taxa, as exemplified in analyses by Mei et al () on seven B. oleracea crops and by Hintum et al () on genebank accessions of white cabbages. Allender et al () found a wealth of diversity revealed by chloroplast SSRs among the Mediterranean wild species, contrasting with an apparent absence of chloroplast diversity in B. oleracea crops and contemporary UK natural populations of B. oleracea .…”
mentioning
confidence: 99%